Representation of Black Girl Discovering Self-Esteem in Akeelah and The Bee Film - Dewi, Nurmala; Tati Mardewi; Furi Indriyani (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This research aims to discover the self-esteem portrayed in Akeelah and the Bee film by Doug Atchison. The film's theme is about Akeelah Anderson achieving success in a spelling bee competition and having a challenge to build her self-esteem. Self-esteem is a person’s overall sense of self-worth or personal value. It significantly influences motivation, behavior, and overall well-being. Collectively these characters graphically portray a powerful theme regarding academic motivation. This study employs a qualitative approach which focuses on content analysis. The analysis of self-esteem is applied by using four aspects of Coopersimth’s self-esteem namely competence, power, significance, and virtue. Each aspect is elaborated based on the scripts and depicts self-esteem regarding the theory. As a result, Akeelah has all aspects of self-esteem in her personality that help her to achieve her goal. The important message sent to the audience is that Akeelah’s story demonstrates self-esteem is not something we are born with, but rather something we build through challenges, support from others, and a belief in our abilities